Contribuição ao estudo dos mecanismos resistentes à força cortante em lajes alveolares protendidas - Marquesi, Matheus Lorena Gonçalves (2014)
In this work flexure shear and tension shear are studied. It is presented a literature review with emphasis on the major normative recommendations about the shear strength in elements without shear reinforcement. Concerning flexure shear capacity considerations are made about the tensile strength of high strength concrete by analysis of 39 experiments. This samples were collected in the literature and are presented herein. Furthermore, it is proposed to consider the variable influence of prestressing on the shear strength. With respect to tension shear, it is proposed the coefficient b, which seeks to improve the traditional models considering indirectly the influence of shear stresses in transmission length. 49 international experiments are analyzed to validate this coefficient and it is concluded that the modified models show significant improvements. Yet developed an experimental program were tested 15 hollow core slabs varying the distance between the edge of the slab and its nearest support. All failures were by tension shear. The transmission length established by NBR14861 was considered adequate for the tested slabs by correlation with tension shear test results.